Virtual screening of antibacterial compounds by similarity search of Enoyl-ACP reductase (FabI) inhibitors - Junior, Leonardo Rander Asse; Kronenberger, Thales; Serafim, Mateus Sá Magalhães; Sousa, Yamara Viana; Franco, Isabella Drumond; Valli, Marilia [UNESP]; Bolzani, Vanderlan Da Silva [UNESP]; Monteiro, Gustavo Claro [UNESP]; Prates, João Lucas Bruno [UNESP]; Kroon, Erna Geessien; Mota, Bruno Eduardo Fernandes; Santos Ferreira, Diego Dos; et al. (Taylor & Francis, 2019)
Aim: Antibiotic resistance is an alarming issue, as multidrug-resistant bacteria are growing worldwide, hence the decrease of therapeutic potential of available antibiotic arsenal. Among these bacteria, Staphylococcus aureus was pointed by the WHO in the pathogens list to be prioritized in drug development. Methods: We report the use of chemical similarity models for the virtual screening of new antibacterial with structural similarity to known inhibitors of FabI. The potential inhibitors were experimentally evaluated for antibacterial activity and membrane disrupting capabilities. Results & conclusion: These models led to the finding of four new compounds with antibacterial activity, one of which having antimicrobial activity already reported in the literature.
Keywords: antibacterial; FabI inhibitors; ligand-based virtual screening; MRSA; similarity search; Staphylococcus aureus